Testosterone levels in men with type 2 diabetes mellitus - Chaudhary, Satish; Kaushik, Madan; Jaswal, V. M. S.; Raina, Rajeev; Thakur, Roshan; Thakur, Manish Kumar; Sharma, Ritin (International Journal of Research in Medical Sciences, 2018)
Background: To study testosterone levels in men with type 2 diabetes mellitus in age group of 30-50 years. Methods: In this cross sectional study of 193 type 2 diabetes men aged between 30-50 years, total and free testosterone levels were calculated along with other relevant clinical variables like hypertension, BMI, dyslipidemia, peripheral neuropathy, retinopathy. Results: The study group had study out of 193 patients 34.7% have low total testosterone levels, 29.53% have low free testosterone levels and 23.3% have both low and free testosterone levels. Maximum number of patients with low total testosterone levels were in the age group between 46-50 years (41.0%) and with low free total testosterone levels were in the age group between 36-40 years (41.8%). Conclusions: Type 2 diabetes mellitus is associated with low levels of total and free testosterone. Obesity and dyslipidemia are also associated with low testosterone levels.